Effect of Dezocine on Hemodynamic Indexes of Postoperative Patients With Traumatic Brain Injury (TBI)---A Pilot Study - Xuejian Wang; Yang Chen; Zhifeng Wang; Yi Zhang; Zhiming Cui; Chen Sun (Frontiers in Pharmacology, 2022)
Background: Due to pain and other stimuli, patients with traumatic brain injury (TBI) after surgery show excited Sympathetic Nervous system, increased intracranial pressure, brain tissue swelling, intracranial hemorrhage, or reduced cerebral perfusion pressure, seriously threatening the life and prognosis of patients. The effect of dezocine on postoperative analgesia after TBI remains largely undetermined.Objective: In the present study, we aimed to investigate the efficacy and safety of dezocine in postoperative sedative and analgesic therapy for a craniocerebral injury.Methods: The patients were randomly divided into two groups (n = 40) as follows: dezocine group (Group A) and control group (Group B). Electrocardiography (ECG), heart rate (HR), blood pressure, and oxygen saturation (SpO2) were routinely monitored after postoperative return to the ward. Both groups were initially injected with 5 mg·kg−1·h−1 propofol to maintain sedation, and the dose was adjusted according to the patient’s condition. Vital signs of patients were recorded at T1 (the base value when arriving at the ward), T2 (before the sedative agent was used) and T3 (use of dezocine or 0.9% saline solution for 8 h), T4 (use for 1 day), T5 (use for 3 days), T6 (termination of dezocine or 0.9% saline solution for 1 day), and T7 (termination for 3 days), and mean arterial pressure (MAP) and HR values were also recorded. The total amount of propofol, total fluid inflow, blood loss, and urine output were recorded within 24 h. The number of coughs of each patient was recorded within 1 day after entry, and the incidence of adverse events, such as insufficient oxygenation (SaO2 reduced by about 5% from the base value), hypotension, bradycardia, laryngospasm, bronchospasm, and so on, was assessed.Results: Compared with the control group (group B), the hemodynamics of the dezocine group (group A) was more stable, there were significant differences in MAP and HR (p < 0.05), and the stress response was milder. The total amount of propofol, total fluid inflow, blood loss, and urine volume of the dezocine group were significantly improved compared with the control group (p < 0.05). Moreover, the incidence of adverse events, such as cough, in the dezocine group was significantly reduced compared with the control group (p < 0.05).Conclusions: Dezocine, as a drug with a strong analgesic effect and obvious sedative effect, was suitable for craniocervical surgery, and it could significantly improve the stability of airway and hemodynamics in TBI patients during anesthesia recovery.